Artificial intelligence related safety issues associated with FDA medical device reports - Jessica L. Handley; Seth A. Krevat; Allan Fong; Raj M. Ratwani (npj Digital Medicine)
Abstract The Biden 2023 Artificial Intelligence (AI) Executive Order calls for the creation of a patient safety program. Patient safety reports are a natural starting point for identifying issues. We examined the feasibility of this approach by analyzing reports associated with AI/Machine Learning (ML)-enabled medical devices. Of the 429 reports reviewed, 108 (25.2%) were potentially AI/ML related, with 148 (34.5%) containing insufficient information to determine an AI/ML contribution. A more comprehensive approach is needed.